2007
DOI: 10.1089/tmj.2006.0023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Underutilization of Videophones in Hospice Settings

Abstract: The aim of this study was to evaluate hospice providers' attitudes and perceptions regarding videophone technology in settings where the technology was introduced but underutilized. Specifically, the project seeks to provide an in-depth understanding of attitudes and perceptions that may lead to failure of a telehealth implementation in the hospice setting in the context of the technology acceptance model. Two hospice agencies were selected as a purposive sample. Both agencies had acquired videophones that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 16 publications
0
37
1
1
Order By: Relevance
“…19 Issues to address include technical difficulty, perceived expense, and acceptance by providers and patients. 20,21 The image quality of current videophones using commercial telephone lines may not offer adequate resolution to detect important clinical changes. To overcome this and the lack Higher scores indicate worse quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…19 Issues to address include technical difficulty, perceived expense, and acceptance by providers and patients. 20,21 The image quality of current videophones using commercial telephone lines may not offer adequate resolution to detect important clinical changes. To overcome this and the lack Higher scores indicate worse quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…They had to quantitatively test relationships between variables specified by TAM. This criterion excluded studies that measured TAM variables but not the relationships between them [64-71] and qualitative studies that used TAM as a framework [72, 73]. Unlike Yarbrough and Smith [30], who reviewed qualitative studies of TAM, we were interested specifically in studies of TAM, a model of quantitative relationships between variables.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, qualitative TAM studies can be informative. Day et al’s qualitative interview study of hospice providers’ use of videophones showed that providers perceive videophone technology as useful (improved communication, better access to care) but not easy to use (low technical quality, difficult to use for patients), and that ease of use appeared to be a more dominant contributor to intentions to use [73]. Karsh et al’s study of primary care physicians’ and nurses’ perceptions of using error reporting systems revealed perceptions of usefulness (improved care, suggestions for improvement) and ease of use (easy and quick to use, minimal extra workload, good instructions), as well as subjective norms (colleagues, supervisors, internal and external organizations) [72].…”
Section: Methodsmentioning
confidence: 99%
“…The model suggests that perceived usefulness and perceived ease of use influence users’ attitudes toward using the technology and contribute to their behavioral intention to use the technology. TAM has been applied in healthcare to understand clinicians’ technology adaptation in healthcare environment and evidence regarding its usefulness to predict clinicians’ acceptance of a new technology is mounting 1418…”
Section: Introductionmentioning
confidence: 99%